2019
DOI: 10.1016/j.ajhg.2019.03.001
|View full text |Cite|
|
Sign up to set email alerts
|

Truncating Mutations in UBAP1 Cause Hereditary Spastic Paraplegia

Abstract: The diagnostic gap for rare neurodegenerative diseases is still considerable, despite continuous advances in gene identification. Many novel Mendelian genes have only been identified in a few families worldwide. Here we report the identification of an autosomal-dominant gene for hereditary spastic paraplegia (HSP) in 10 families that are of diverse geographic origin and whose affected members all carry unique truncating changes in a circumscript region of UBAP1 (ubiquitin-associated protein 1). HSP is a neurod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…PCR of c.DNA, synthesized from RNA isolated from the same individual, showed that mRNA escapes nonsense mediated decay (Fig. 1d), as previously reported [4].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…PCR of c.DNA, synthesized from RNA isolated from the same individual, showed that mRNA escapes nonsense mediated decay (Fig. 1d), as previously reported [4].…”
Section: Resultssupporting
confidence: 85%
“…Here, we describe 13 patients from 7 families with HSP recruited to the 100KGP, who carry 3 truncating variants in UBAP1, a newly identified gene that causes pure forms of juvenile HSP [4]. Variant interpretation analysis had been initially carried out via the 100KGP automated pipeline in known HSP genes [5], and failed to identify a genetic diagnosis in all families.…”
Section: Introductionmentioning
confidence: 99%
“…UBAP1 is a member of the UBA domain family, which includes proteins that have a role in the ubiquitin and ubiquitination pathways (Qian et al, 2001). Seeking to unveil the effects of mutations in UBAP1 in vivo, Farazi Fard et al 2019found that microinjection of CRISPR/Cas9 and sgRNAs against UBAP1 in the transgenic fish with fluorescently labeled motor neuron Tg(Oligo2::DsRed) resulted in misshapen axons and shorter motor neuron length compared with what was observed in controls (Farazi Fard et al, 2019). This work further reinforced the suggestion that "UBAP1 links endosomal trafficking to the ubiquitination machinery pathways that have been previously implicated in HSPs.…”
Section: Spg80mentioning
confidence: 85%
“…SPG80 is a juvenile-onset neurological disorder characterized by a progressive spasticity and hyperreflexia. Some affected subjects also showed cerebellar signs and mild cognitive impairment (Farazi Fard et al, 2019). All affected individuals carried heterozygous non-sense or frameshift mutations in the UBAP1 (ubiquitin-associated protein 1) gene.…”
Section: Spg80mentioning
confidence: 99%
“…We report frameshift UBAP1 variants in five individuals with childhood-onset AD HSP. While preparing this manuscript, an article describing truncating variants in UBPA1 causing HSP was published (Farazi Fard et al, 2019), with eight different truncating mutations from 10 families, including a recurrent de novo c.426_427delGA variant in two families, which is identical to the variant in Families 1-4 reported here (Table 1). Therefore, with our patients, there are now six HSP families with the c.426_427delGA variant identified, providing additional evidence for a mutational hotspot in UBAP1.…”
Section: Discussionmentioning
confidence: 99%